Dialogue with Another as a Form of Self-Identification of the Lyrical Subject of N. Gambar - Amineva, Venera (Przegląd Wschodnioeuropejski, 2018)
Lyrics of the Tatar poet N. Gambar was the subject of the research. His creative activity depicted the leading tendencies of the national historic-literary process at the end of ХХ – beginning of ХХI centuries. Intertextuality became one of the Gambar’s poetic techniques determining his unique creative manner. The present article considers it as a form of a lyrical subject self identification. The works on intertextuality by Yu. Kristeva, G. Genette, as well as the works by B. O. Korman, S. N. Broitman, which determine the principles of subject sphere organization in the lyrical work, influenced the concept of research. System and structure-based and context-hermeneutic approaches were applied for the solution of the set of objectives. It was determined that the Gambar lyrical subject’s self identification as the bearer of the overall generic substance of the mankind, as a representative of a certain ethnos, unique individuality and, finally, as a poet and a demiurge occurs in the dialogue with the Other.